Cellular analysis of the action of epigenetic drugs and probes. Issue 5 (4th May 2017) - Hau, Mirjam; Zenk, Fides; Ganesan, A.; Iovino, Nicola; Jung, Manfred
ABSTRACT: Small molecule drugs and probes are important tools in drug discovery, pharmacology, and cell biology. This is of course also true for epigenetic inhibitors. Important examples for the use of established epigenetic inhibitors are the study of the mechanistic role of a certain target in a cellular setting or the modulation of a certain phenotype in an approach that aims toward therapeutic application. Alternatively, cellular testing may aim at the validation of a new epigenetic inhibitor in drug discovery approaches. Cellular and eventually animal models provide powerful tools for these different approaches but certain caveats have to be recognized and taken into account. This involves both the selectivity of the pharmacological tool as well as the specificity and the robustness of the cellular system. In this article, we present an overview of different methods that are used to profile and screen for epigenetic agents and comment on their limitations. We describe not only diverse successful case studies of screening approaches using different assay formats, but also some problematic cases, critically discussing selected applications of these systems.